Management of Hypertension and Diabetes Mellitus in Patients with Target Organ Damages and/or Previous Cardiovascular Diseases in Lebanon. Where do We Stand with Respect to International Guidelines? - Kekedjian, Jeannot; Challita, Raymond; Abdallah, Mikael Abi; Chahine, Mirna N; Asmar, Roland (Cardiology and Cardiovascular Medicine, 2020)
Background: Hypertension and diabetes are major health problems worldwide. They can coexist together increasing the complication rates. The increased incidence of these complications in the Lebanese population reflects a poor disease control, consequently increased risk of death. Objective: The aim of this study was to assess Lebanese physicians’ compliance to international guidelines and their control on diabetes and hypertension. Methods: Retrospective cross-sectional study was conducted on 750 Lebanese patients randomly selected from 6 university hospitals from January 2014 to August 2015. Patients were divided according to their medical history: 252 hypertensive, 249 diabetic, 249 both hypertensive and diabetic. All patients had target organ damages and were admitted to the hospitals. Results: Our study showed the overuse of beta blockers in hypertensive and diabetic patients, while neglecting lifestyle modifications and the drug of choice for special populations. A proportion of 7% of hypertensive patients in the Lebanese population were untreated for their hypertension. The first line treatment for diabetic patients was respected in most of the patients. However, results showed those with diabetes were not properly controlled. Aspirin was only used in half of the patients, though all of them were high-risk with target organ damages. Discussion: Results from this study in Lebanon indicate the absence of adherence to guidelines by the Lebanese physicians, especially in the management of hypertension where beta blockers were overused, in addition to the absence of control of diabetes and hypertension, which may be due to physicians’ non adherence to guidelines or patients’ noncompliance to medications.